ENTREPRENEURSHIP TRAINING FOR MSME ACTIVITIES BASED ON CREATIVE ECONOMY DURING THE COVID-19 PANDEMIC IN SERANG CITY - Nani Rohaeni; Dini Martinda Lestari; Surachman Surachman; Supatmin Supatmin; Pramudi Harsono; Fatari Fatari (Yayasan Education and Social Center, 2022)
Micro, Small and Medium Enterprises (MSMEs) are businesses that play an essential role in increasing Gross Domestic Product (GDP) in Indonesia, facing the industrial era 5.0. Currently, MSMEs are facing global competition to stay in the market. In addition, the COVID-19 pandemic that has attacked Indonesia since the beginning of 2020 has made the MSME sector collapse. Therefore, he needs strategies from various parties to produce MSMEs to survive the pandemic and compete in the global market. This community service aims to provide services to micro, small and medium enterprises (MSMEs) who wish to maintain and develop their business during economic competition and the COVID-19 pandemic period by optimizing the use of technology in their activities. The method used to implement community service is service and assistance to meet needs through business enthusiasm and marketing training with micro-small and medium enterprises (MSMEs) with zoom meetings. The target of community services is focused on entrepreneurship training for MSME players based on the creative economy and programs to create social media and websites for marketing MSME products. With training, community service activities are transparent and can continue to be a standard MSME service to continue to meet the needs of MSMEs